PENGARUH SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS INFORMASI AKUNTANSI KEUANGAN (Studi Pada Satuan Kerja Di Wilayah Kantor Pelayanan Pembendaharaan Negara Kendari) - Muzaddik, Muzaddik (JURNAL AKUNTANSI, 2017)
ABSTRACTThis study aims to determine if the human resources and internal controls affect the quality of financial accounting information. This study was qualitative. The mehtod of data collection in this study was questionnaire. The result showed that the human resources affects the quality financial accounting information with the value of regression coefficient of 0.160 and a significance 0f 0.018 (alfha 0.05). The internal control affects the quality of financial accounting information with the value of regression coefficient of 0.173 and significance of 0.030 (alfha 0.05). while the value of R Square was equal to 0.760, which means by 76% independent variables in this study could affect the dependent variables. Keywords : Human Resources, Internal Control, The quality of Financial information.